A Subdued Demon in Exodus 15:7-8 - Korpel, Marjo C. A. (Vetus Testamentum, 2019)
The Song of the Sea is long known to contain allusions to mythological motifs related to Canaanite religion that have been adapted to the faith of Israel. On the basis of a recent study of the Ugaritic texts KTU 1.107 and 1.100 it is shown that Exod 15:7-8 falls in this category of reinterpretation. It is proposed to render verse 7b you sent your Ḥoron, he devoured them like stubble'. Suffixed personal pronouns with the names of deities are attested in Ugarit and ancient Hebrew inscriptions. However, in Exod 15 Ḥoron has been reduced to a redoutable assistant of God, an executioner called up to punish God's opponents.